Path Loss Modeling of WLAN and WiMAX Systems - Imran Israr; Mahmood Ashraf Khan; Shahzad A. Malik; Shahid A. Khan; Mustafa Shakir (International Journal of Electrical and Computer Engineering (IJECE), 2015)
With the advancement in technology, there was need for efficient and high speed internet through which we could have access to multiple networks as per the user requirement. WLAN met this need to some extent but, due to its low range it was not recommended commercially. With the introduction of WiMAX there was an emerging need to select the best network amongst WiMAX or WLAN depending upon the user location. Pathloss with respect to these particular networks also needs to be compared. In this paper we compare the pathloss modelling for WiMAX and WLAN systems. Different Models have been compared with each other to know which model performs better by keeping same simulation environment. Path Loss models used for WLAN are Okumura, Hata, Cost-231 and Free Space Path Loss whereas models used for WiMAX are Free Space Path Loss, Okumura-Hata, Cost231-Hata and Stanford University Interim. In case of WiMAX three different scenarios Urban, Sub-Urban and Rural is considered where as in case of WLAN only outdoor environment is considered. With the Path Loss comparison, power received for these two technologies; WiMAX, and WLAN is also simulated. MATLAB is the tool used for simulations. Antenna Specifications for WiMAX and WLAN is kept same for all simulation environments.